Extensões de Homomorfismos de Subgrupos a Endomorfismos do Grupo - Guimarães, Bruno Formiga (2010)
Bertholf and Walls provided a characterization for the class of groups quasi-injective finite. Furthermore, Juriaans, Bastos Azevedo and give a rating for the injective type groups, which are a distinct class of the former despite being quite close.